Ammonium‐Ion Storage Using Electrodeposited Manganese Oxides - Song, Yu; Pan, Qing; Lv, Huizhen; Yang, Duo; Qin, Zengming; Zhang, Ming‐Yue; Sun, Xiaoqi; Liu, Xiao‐Xia (Angewandte Chemie International Edition, 2021)
NH4+ ions as charge carriers show potential for aqueous rechargeable batteries. Studied here for the first time is the NH4+‐storage chemistry using electrodeposited manganese oxide (MnOx). MnOx experiences morphology and phase transformations during charge/discharge in dilute ammonium acetate (NH4Ac) electrolyte. The NH4Ac concentration plays an important role in NH4+ storage for MnOx. The transformed MnOx with a layered structure delivers a high specific capacity (176 mAh g−1) at a current density of 0.5 A g−1, and exhibits good cycling stability over 10 000 cycles in 0.5 M NH4Ac, outperforming the state‐of‐the‐art NH4+ hosting materials. Experimental results suggest a solid‐solution behavior associated with NH4+ migration in layered MnOx. Spectroscopy studies and theoretical calculations show that the reversible NH4+ insertion/deinsertion is accompanied by hydrogen‐bond formation/breaking between NH4+ and the MnOx layers. These findings provide a new prototype (i.e., layered MnOx) for NH4+‐based energy storage and contributes to the fundamental understanding of the NH4+‐storage mechanism for metal oxides. NH4+ storage using electrodeposited manganese oxides (MnOx) is studied for the first time. MnOx exhibits structural transformation during charge/discharge in dilute ammonium acetate (NH4Ac) electrolyte. Experimental and theoretical results suggest that the reversible NH4+ insertion/deinsertion in layered MnOx is associated with hydrogen‐bond formation/breaking between NH4+ and the MnOx layers.